Training the novice triathlete - Logan, C. (IDEA fitness journal, 2006)
This article will focus on the training needs of the novice triathlete. The main aspects of the article are: - Typical causes and types of Injury - Improving the odds - Tips for a running start - The strength training program/suggested strength training - Other factors in injury prevention.